In Silico Evaluation of Various Signal Peptides to Improve Secretion of Humulin Protein in E. coli Host - Kavousipour, Soudabe; Barazesh, Mahadi; Mohammadi, Shiva; Abdollahpour- Alitappeh, Meghdad; Fallahi, Shirzad; Shakarami, Amir; Hajmohammadi, Zeynab (Current Proteomics, 2021)
Background: Escherichia coli host has been the workhorse for the production of heterologous proteins due to simplicity of use, low cost, availability of various expression vectors, and a plethora of knowledge on its genetic characteristics, but without a suitable signal sequence, this host cannot be used for the production of secretory proteins. Humulin is a form of insulin used to treat hyperglycemia caused by types 1 and 2 diabetes. To improve expression and make a straightforward production of Humulin protein, we chose a series of signal peptides. Objective: The aim of this study was to predict the most excellent signal peptides to express secretory Humulin in E. coli organism. Methods: Therefore, to forecast the most excellent signal peptides for expression of Humulin in Escherichia coli, 47 signal sequences from bacteria organisms were elected and the most imperative elements of them were studied. Hence, signal peptide probability along with physicochemical features was evaluated by signal 4.1, and Portparam, PROSO II servers respectively. Later, the in- -silico cloning in a known pET28a plasmid system also estimated the possibility of best signal peptide+ Humulin expression in E. coli. Results: The outcomes demonstrated that among 47 signal peptides only 2 signal peptides can be considered as suitable signal peptides. Conclusion: Ultimately protein yebF precursor (YEBF_ECOLI) and protein yebF precursor (YEBF_YERP3) were suggested as the most excellent signal peptides to express Humulin (With D scores 0.812 and 0.623, respectively). Although verification of these results warrants experimental analysis.
Keywords: humulin